The Effect of Customer Relationship Management on Customer Satisfaction and Customer Loyalty - Dewa Made Haryandika; I Ketut Santra (Indonesian Journal of Business and Entrepreneurship (IJBE), 2021)
This study aimed to determine the influence of Customer Relationship Management (CRM) which can be indicated as commitment, communication, and quality service, on customer loyalty through customer satisfaction. CRM acted as an independent variable in this study. The sample of this study included 94 respondents who were customers of PT Ritra Cargo Indonesia, Denpasar Branch. The data analysis technique used is path analysis. The result of this study indicated that the coefficient of determination was 0.651 which meant 65.1% of customer loyalty was influenced by CRM and customer satisfaction with a significance value of F (0,000) < α 0,05. This indicated that the effect of CRM on customer satisfaction was significant, the effect of satisfaction on customer loyalty was significant, and the effect of CRM on customer loyalty was significant. Keywords: customer relationship management (crm), customer satisfaction, customer loyalty